Effect of Hyperventilation on Periodic Repolarization Dynamics - Schüttler, Dominik; von Stülpnagel, Lukas; Rizas, Konstantinos D.; Bauer, Axel; Brunner, Stefan; Hamm, Wolfgang (Frontiers in Physiology, 2020)
Heart and lung function are closely connected, and the interaction is mediated by the autonomic nervous system. Hyperventilation has been demonstrated to especially activate its sympathetic branch. However, there is still a lack of methods to assess autonomic activity within this cardiorespiratory coupling. Periodic repolarization dynamics (PRD) is an ECG-based biomarker mirroring the effect of efferent cardiac sympathetic activity on the ventricular myocardium. Its calculation is based on beat-to-beat variations of the T-wave vector (dT°). In the present study we investigated the effects of a standardized hyperventilation maneuver on changes of PRD and its underlying dT° signal in 11 healthy subjects. In response to hyperventilation dT° revealed a characteristic pattern and normalized dT° values increased significantly compared to baseline (0.063 (IQR 0.032) vs. 0.376 (IQR 0.093), p<0.001) and recovery (0.082 (IQR 0.029) vs. 0.376 (IQR 0.093), p<0.001). During recovery dT° remained on a higher level compared to baseline (p=0.019). When calculating PRD, we found significantly increased PRD values after hyperventilation compared to baseline (3.30 (IQR 2.29) deg2 vs. 2.76 (IQR 1.43) deg2; p=0.018). Linear regression analysis revealed that the increase in PRD level was independent of heart rate (p = 0.63). Our pilot data provides further insights in the effect of hyperventilation on sympathetic activity associated repolarization instability.